Criminal justice, wildlife conservation and animal rights in the Anthropocene - Sollund, Ragnhild Aslaug (Bristol University Press, 2024)
"This book addresses one of today's most urgent issues: the loss of wildlife and habitat, which together constitute an ecological crisis. Combining studies from different disciplines such as law, political science and criminology, with a focus on animal rights, the chapters explore the successes and failures of the international wildlife conservation and trade treaties, CITES and the BERN Convention. While these conventions have played a crucial role in protecting endangered species from trade and in the rewilding of European large carnivores, the case studies in this book demonstrate huge variations in their implementation and enforcement across Europe. In conclusion, the book advocates for a non-anthropocentric policy approach to strengthen wildlife conservation in Europe" --